Business Process Modeling of Indonesian Human Milk Bank Based on Bank Framework Using BPMN: Case Study Lactashare - Wahyuningdiyah, Neny (JURNAL AKUNTANSI DAN MANAJEMEN, 2025)
In Indonesia, human milk sharing initiatives have yet to adequately implement the donor process in accordance with medical standards, government regulations, and Islamic law. It is imperative to employ the BANK framework developed by the PATH organization to model the human milk donor business process. The present study employs a comparative method, integrating qualitative and quantitative analysis, to compile a model from various national and global regulatory sources and religious law which visualized through BPMN diagrams, derived from a case study conducted at Lactashare. The simulation findings demonstrate the efficacy and efficiency of the proposed model in comparison to the existing method, with potential savings of up to 32% in total fixed expenses and an operational enhancement of 18 hours and 48 minutes. However, to ensure the validity of the results, a comparison with those obtained using more advanced tools and techniques is necessary. Collaboration among human milk banks in Muslim countries is encouraged to facilitate the exchange of best practices, support research initiatives, and assist policymakers in formulating policy solutions that align with religious law while ensuring the smooth operation of human milk banking.